Identifikasi Bakteri Penyebab Penyakit Utama pada Tanaman Hidroponik - DEWA AYU DIAH PUSPITASARI; I PUTU SUDIARTA; I MADE SUDARMA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Identification of Bacteria Causing the Main Diseases in Hydroponic Plants Hydroponics is a horticultural cultivation technique using water as its growing medium. As the times progressed, people began to switch to planting with a hydroponic system, but this system was not completely free from pathogen attacks, one of which was bacteria. Therefore, this study aims to identify the types of bacteria that can infect hydroponic plants and determine the percentage of disease in hydroponic plants. The research implementation includes (1) calculating the percentage of disease, (2) sampling, (3) symptomatic plant isolation, (4) inoculation, (5) morphological classification, (6) detection of bacteria by PCR (Polymerase Chain Reaction), and sequencing analysis. The results showed that the percentage of attack on three plants, namely lettuce with soft rot symptoms, was 31.6% and celery with bacterial blight symptoms was 56.1%. The highest attack percentage was on tomato plants with bacterial wilt symptoms, reaching 69.1%. PCR results showed DNA bands measuring ± 1500 bp using general 16S rRNA primers (27F forward and 1492R reverse) on the three plants. Sequence analysis was continued on bacterial isolates from tomato plants because they had the highest percentage of attack. The nucleotide analysis of bacterial isolates in tomato plants indicated that the bacteria were a genus of Pseudomonas sp. Homology level of Pseudomonas sp. from Kesiman Village, East Denpasar District, Bali, after being traced and matched to the GenBank data in the NCBI program, it has similar homology with Pseudomonas from Iraq and India with a homology level of 89.86%, as well as from Egypt, New Zealand, and Germany with a sequence homology level of 89.19%.